EMERGING AND FLOATING PLANTS IN THE MANATÍ DIET (FAMILY: TRICHECHIDAE: TRICHECHUS MANATUS) IN THE CARIBBEAN OF COSTA RICA - Gómez-Lépiz, Alexander (2010)
Trips were conducted on different sectors of the Tortuguero National Park in search of traces of food left by the manatees to determine their diet and quantify the use and availability of plants contained in their diet,. In recent browsing sites the proportion of plants was quantified by analyzing the percentages of the plants found in the feeding sites (use) and sampled areas around them (availability). It was determined that two grass species: gamalote (Paspalum repens) and (Urochloa mutica) are plants that the manatees primarily selected for consumption. The present study permitted to determine how the manatee consumes food resources in the area.  This has been the basis for other research requiring information on dietary factors.  There are also other proposals being implemented for baiting and capture techniques in sensitive sites for the conservation of manatees, based on the distribution of the plants that the animals consume  in the area.